Sweden : 2001 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Sweden. (IMF Staff Country Reports; Country Report ;, 2001)
Sweden faces continued slower economic growth in the rest of 2001 followed by a return to potential output in 2002 with the projected global recovery. Even as the economy enters a somewhat subdued phase, inflation is projected to be slightly above the Riksbank's target over a two-year horizon. The macroeconomic policy setup rests on the firm foundations of a fiscal strategy grounded in clear medium-term guidelines and the Riksbank's inflation targeting framework. Fiscal policy is anchored in the authorities' medium-term fiscal rules.